EFEKTIVITAS PENGGUNAAN METODE MNEMONIK DALAM MENINGKATKAN KEMAMPUAN MENGINGAT KANJI DASAR PADA SISWA SEKOLAH MENENGAH ATAS - Nadya Ghina Khalda Indra Putri, - (2023)
Language learning generally has a goal so that students can read the letters of the language and also so that students can understand the language. For Indonesian students whose mother tongue does not use a symbol system, Japanese is a difficult language to learn because Japanese contains four types of letter characters, namely hiragana, katakana, kanji, and romaji which make it difficult for students to memorize all of them. Therefore we need a method so that students can memorize Japanese letters properly and effectively using the loci technique mnemonic method. This study aims to determine whether using the loci technique mnemonic method can improve the ability to remember basic kanji in high school students. The method used is a true experimental design using instruments in the form of tests and questionnaires. The sample in this study was 36 students consisting of 18 XI MIPA 7 students as the control class and 18 XI MIPA 3 students as the experimental class. Based on the results of data analysis, a t-count of 2.94 was obtained while the t-table for db = 35 with a significance level of 5% = 2.03 and a t-table with a significance level of 1% = 2.72. Because the t-count is greater than the t-table, the working hypothesis (Hk) is accepted. So it can be concluded that there is a significant difference between the learning outcomes of remembering basic kanji before and after using the loci technique mnemonic method. Based on the results of the questionnaire analysis, it was found that the majority of respondents gave positive responses regarding the use of the loci technique mnemonic method in learning basic kanji so that this method can be used as an alternative in improving the ability to remember basic kanji in high school students.